Concepções de professores e o ensino de probabilidade na escola básica - Gonçalves, Mauro César (2004)
The Aim of our research was to identify the current Mathematics teachers conceptions of probability and to verify if there is a relation between these conceptions and the ones used in the 1970s, 1980s and 1990s.To do so, our work was done through studies and analyses of didaction books and institutional organization since the 1970s, having theYves Chevallard (1995) Praxeology Organisation as a source, which provided us with conditions to identify the different tendencies related to the Probability teaching. This analysis contributed directly to our studies of Didactical Transposition along with Probability according to Yves Chevallard s proposals and identifying the Pedagogical Knowledge and the one used at school. As a part of our research we had twenty teachers answer a questionnaire which was divided into two parts. The first one was to acquire information about their profile; and the second one was about their own conception of Probability. The results were related to the conceptions presented by Goded (1996) and the different periods of the Probability teachings by means of the software C.H.I.C. This way, we could obtain simultaneously, information related to the type of conception and period of basic formation. On the whole, the analysis of the obtained information enabled us to say that there is evidence that Teachers actions influence the conception changes, inasmuch as teachers, who had their basic education in the same period and teach different levels have, too, different conceptions